Implementasi Program Posyandu Lansia oleh Tim PKK di Kelurahan Tanjung Sari Kota Medan - Ayunita, Aprilyani; Kadir, Abdul; Matondang, Armansyah (Universitas Medan Area, 2024)
The Elderly Integrated Service Post (Posyandu Lansia) is a form of integrated service for the elderly (elderly) which is mobilized by the Family Empowerment and Welfare Mobilization Team (PKK). The purpose of this study was to determine the implementation of the integrated elderly service post program by the PKK activator team in Tanjung Sari Village, Medan Selayang District, Medan City and its inhibiting factors. The theory used is G. Edward III, namely Communication, Resources, Disposition and Bureaucratic Structure. The research method used is a qualitative method by means of observation, interviews and documentation. The results showed that the implementation of the posyandu program for elderly by PKK TP in Tanju ng Sari Village, Medan Selayang District, Medan City was not effective. Lack of communication between cadres and the community, still unable to utilize the potential of natural resources, lack of responsibility or duties and functions of what they are responsible for, and lack of disrespect for cadres according to their abilities and knowledge.